Synthesis and Spectral Investigation of the Complex of S4N3Cl with Fe(CH3COO)2.4H2O - Upadhyay, Shalini; S. Jadon, S.P (Asian Journal of Chemistry, 2010)
On the basis of its mass, IR and XRD spectra, the complex of S4N3Cl with Fe(CH3COO)2 synthesized, is found to be a hexadentately coordinated complex, having triclinic geometrical array.